Brazilian Headache Congress 2024 Between Socrates and Silicon: The odyssey of knowledge - Jesus, Alan Chester Feitosa de (Headache Medicine, 2024)
Chronicle about the latest Brazilian Headache Congress, held in Foz do Iguaçu in August 2024.